Deteksi Dini dan Upaya Penanggulangan Resiko Depresi Perinatal dengan Skala Maternal Blues Suryani - Suryani Manurung; Pangastuti, Tri Endah; Ellya Netty (Ilin Institute, 2021)
The purpose of community service activities is to detect and overcome the risk of perinatal depression. The methods used are 1) Detection of the risk of perinatal depression with the Suryani maternal blues scale, 2) Dissemination of the problems found 3) Health promotion for pregnant and postnatal periods to recognize the risk of depression in pregnant and postpartum women, the impact of depression on pregnant women and postpartum as well as preventive and promotive efforts. Location RW 08 Kelurahan Ragunan Kec. South Jakarta Sunday Market. Implementation time from June to September 2021. The results of community service activities obtained that the risk of depression in pregnant women was mostly primiparous at 63.6% with a first trimester gestational age of 80%. The risk of postpartum blues is 28.6 in late teens. There is no significant relationship between the factors of age, gestational age and postpartum with the source of support for the incidence of depression risk of pregnancy and postpartum. Preventive and promotive efforts with participants' health promotion actions were given pretest and posttest, obtained significant results between pre and posttest. The results obtained illustrate that the psychological condition of the mother during the perinatal period is at risk for depression and postpartum blues. However, this condition is strongly supported by the existence of sources of support, information obtained by mothers during pregnancy and after childbirth. One of the factors that can maintain the mother's emotional and mental condition remains good. So as not to damage the bonding relationship between mother and baby.